2018
DOI: 10.1007/s00586-018-5853-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel unilateral C1 double screw and ipsilateral C2 pedicle screw placement combined with contralateral laminar screw–rod fixation for atlantoaxial instability

Abstract: Purpose To investigate the anatomical and biomechanical feasibility of the unilateral C1 double screw [pedicle screw (PS) + lateral mass screw (LMS)] and ipsilateral C2 PS combined with contralateral C2 laminar screw (LS)-rod fixation for atlantoaxial instability by comparison with traditional posterior fixation methods. Methods Fifteen sets of complete dry bony specimens of atlas were used for morphometric analysis. The working length, width and thickness of the C1 PSs and LMSs were manually measured. Ten fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…At the final follow-up, occipital-neck pain (VAS score: 0.9 ± 1.9 points, 0.9 ± 1. At present, posterior bilateral short-segment screw fixation and fusion is the commonly performed surgical technique for atlantoaxial fracture-dislocation because the procedure can achieve strong biomechanical stability and definite clinical effect [5][6][7][8][9][10][11][12]. However, if bilateral fixation is performed in patients with high straddles, stenosis, and occlusion of the unilateral vertebral artery caused by an anatomical variation, it is easy to impair the vertebral artery on the dominant side, which results in severely insufficient blood supply to the bilateral vertebral artery and leads to serious consequences, such as ischemic hypoxic encephalopathy [2,14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the final follow-up, occipital-neck pain (VAS score: 0.9 ± 1.9 points, 0.9 ± 1. At present, posterior bilateral short-segment screw fixation and fusion is the commonly performed surgical technique for atlantoaxial fracture-dislocation because the procedure can achieve strong biomechanical stability and definite clinical effect [5][6][7][8][9][10][11][12]. However, if bilateral fixation is performed in patients with high straddles, stenosis, and occlusion of the unilateral vertebral artery caused by an anatomical variation, it is easy to impair the vertebral artery on the dominant side, which results in severely insufficient blood supply to the bilateral vertebral artery and leads to serious consequences, such as ischemic hypoxic encephalopathy [2,14].…”
Section: Resultsmentioning
confidence: 99%
“…However, few studies have compared the clinical efficacy of unilateral and bilateral pedicle screw fixation and fusion in treating atlantoaxial fracture-dislocation. Whether the unilateral procedure can achieve satisfactory results is yet to be explored [ 8 , 9 , 10 , 11 , 12 ]. This study compares the two surgical methods’ clinical results to examine the feasibility of the unilateral procedure.…”
Section: Introductionmentioning
confidence: 99%
“…For the atlas, there are other possible alternative trajectories different from the lateral mass screw of C1, but requiring high level of expertise and experience such as the supralaminar C1 lateral mass screw. [ 7 ] When the reinforcement of the instrumentation is needed, the double C1 ipsilateral mass screws[ 8 ] not being an affordable alternative at any spine center.…”
Section: Discussionmentioning
confidence: 99%
“…To date, C2 pedicle screws have been the first choice for treatment in the clinic. The configuration of C1 and C2 pedicle screws provides optimal biomechanical stability in the screw rod system [2,3]. However, some studies [18,19] have indicated difficult implantation of C2 pedicle screws due to the size of the pedicle, variations in foramen transversarium and variations in the vertebral artery.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the connecting rods sit on the left and right sides, forming an approximate "II" shape. Some biomechanical reports [2,3] have indicated that the screw rod system consisting of C1 bilateral pedicle and C2 pedicle screws can provide firm biomechanical Both are the first authors Feng Qiu, Xiao-Bao Zhou make equal contribution to this work. stability.…”
Section: Introductionmentioning
confidence: 99%